THE Roles and Challenges of Social Workers in Elderly Care: A Qualitative Study of the ATENSI-LU Program at STPL Bekasi, Indonesia - Dwi Heru Sukoco; Elin Herlina (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2024)
The purpose of this study is to determine, explain, and analyze the role of social workers in the elderly social rehabilitation assistance program (ATENSI-LU), especially the role of social workers in implementing the stages of the service process and providing assistance to the elderly. This research design is descriptive-qualitative research. The informants were social workers, the elderly, and the head of the institution (supervisor of social workers). The data collection techniques used were focus group discussions, interviews, observations, and documentation studies. Data validity used tests of credibility, transferability, dependability, and confirmability. The data analysis technique used the Miles and Huberman model, namely data reduction, data presentation, and conclusion drawing. The role of social workers in the ATENSI-LU program is quite good, because they have been able to carry out eleven roles, namely as: Enabler, Broker, Advocate, Mediator, Negotiator, Educator, Initiator, Empowerer, Coordinator, Researcher, and Group facilitator, but there are two roles that have not been implemented, namely the role of Activist and Public speaker. This is because social workers depend on the assignment of the head of the institution and budget availability. Social workers lack the courage to innovate and be creative in making policy improvements to improve the quality of services and assistance, and fulfill the needs and rights of the elderly. Social workers assume that the task of informing the problems and needs of the elderly is the task of the head of the institution. The role of social workers still needs to be improved because: (1) Not all types of social worker roles can be implemented, (2) Social workers have not been able to carry out each role optimally, (3) Social workers focus more on administration to reduce inspection findings, and (4) The program is implemented by all employees, making it less professional. To improve the role of social workers then: (1) Social workers need to better master the program, be more sensitive and concerned about receiving complaints from the elderly, and fight for the fulfillment of the needs and rights of the elderly. (2) STPL Bekasi needs to establish cooperation to improve and develop the capacity of social workers. (3) The Ministry of Social Affairs needs to socialize the program, coordinate, and improve and develop the capacity of social workers.